The Viking Press. Issue 5 (October 2021) - Ghigiarelli, Jamie J.; Berrios, Xavier M.; Prendergast, James M.; Gonzalez, Adam M.
Abstract : ABSTRACT: The Viking press exercise is an upper-body strength and power movement with several potential benefits for athletes. The aim of this article is to describe proper exercise technique and introduce variations for the Viking press. Abstract : Supplemental Digital Content is Available in the Text.